2017
DOI: 10.1007/s00192-017-3434-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and reasons for help-seeking behavior among women with urinary incontinence

Abstract: Only a small proportion of women with UI had consulted a physician, and the driving forces for help-seeking behavior were severity and duration of UI and actively seeking information regarding UI. Public information campaigns might enhance consultation rates providing that passively receiving and actively seeking information have the same effects on help-seeking behavior. We show for the first time that reasons for not consulting a physician for UI vary depending on the severity of the UI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 28 publications
9
32
0
Order By: Relevance
“…In contrast to the non-help-seekers (28.4%), most of the help-seekers (85.7%) thought that without help their UI would remain the same or deteriorate post-partum. This is consistent with Schreiber et al who reported that women who are afraid that their UI will get worse are triggered to seek help [22].…”
Section: Principal Findingssupporting
confidence: 90%
“…In contrast to the non-help-seekers (28.4%), most of the help-seekers (85.7%) thought that without help their UI would remain the same or deteriorate post-partum. This is consistent with Schreiber et al who reported that women who are afraid that their UI will get worse are triggered to seek help [22].…”
Section: Principal Findingssupporting
confidence: 90%
“…In addition, the present study found that scores on the IIQ‐7 and for the physical activity, traveling, social relations and mental health domains were lower for individuals who did not see a doctor because they thought that urinary leakage was normal. In other studies, individuals with higher scores on life quality scales that indicate their life is negatively affected by UI more often see a doctor . Thus, in the present study, although individuals whose QoL was negatively affected by UI visited a doctor, those who were less affected believed that UI is a natural result of aging.…”
Section: Discussionsupporting
confidence: 44%
“…In other studies, individuals with higher scores on life quality scales that indicate their life is negatively affected by UI more often see a doctor. 10,25,[30][31][32][33][34] Thus, in the present study, although individuals whose QoL was negatively affected by UI visited a doctor, those who were less affected believed that UI is a natural result of aging.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, a possible explanation for our finding is that women with diabetes and severe UI might have been excluded from the current study due to having experience of treatment, such as medication and/or surgery for UI, which was one of the exclusion criteria for our study. It is well established in the literature that the severity of UI in women is significantly associated with seeking treatment [ 16 ]. Since the severity of UI was not examined in our study, more studies investigating the association between DM and UI in older women are needed.…”
Section: Discussionmentioning
confidence: 99%